(untitled) (Research, Society and Development, 2024)
The objective of the present study is to evaluate the availability of students, preceptors and tutors at PET Saúde - Gestão e Assistência Araguaia for shared learning with students and professionals from other areas. As a method, evaluative research, descriptive and quantitative approach was used. 43 members of the team implementing PET-Saúde Gestão e Assistência Araguaia participated in the study. The Readiness Interprofessional Learning Scale (RIPLS) questionnaire was applied, validated by Peduzzi and collaborators, with 29 items measured on a Likert scale, addressing concepts related to teamwork and collaboration, professional identity and patient-centered care. The responses were compiled in a Microsoft 365 Excel spreadsheet and analyzed using general and group values of the mean, score and standard deviation of the scores. In the results, the majority of participants were students 28 (63.6%). There is availability for shared learning regarding teamwork and collaboration, professional identity and patient-centered care. The overall score on the availability for shared learning scale was high, 114.65 out of 145 possible points. It is concluded that there was a positive assessment of availability for shared learning with students and professionals from other areas. The readiness demonstrated for interprofessional learning suggests that educational initiatives that promote interprofessional collaboration are being well received and have the potential to positively shape professional training and work culture in health services for more comprehensive and problem-solving assistance.